A review of disease progression models of Parkinson's disease and applications in clinical trials. Issue 7 (26th May 2016) - Venuto, Charles S.; Potter, Nicholas B.; Ray Dorsey, E.; Kieburtz, Karl
ABSTRACT: Quantitative disease progression models for neurodegenerative disorders are gaining recognition as important tools for drug development and evaluation. In Parkinson's disease (PD), several models have described longitudinal changes in the Unified Parkinson's Disease Rating Scale (UPDRS), one of the most utilized outcome measures for PD trials assessing disease progression. We conducted a literature review to examine the methods and applications of quantitative disease progression modeling for PD using a combination of key words including "Parkinson disease, " "progression, " and "model." For this review, we focused on models of PD progression quantifying changes in the total UPDRS scores against time. Four different models reporting equations and parameters have been published using linear and nonlinear functions. The reasons for constructing disease progression models of PD thus far have been to quantify disease trajectories of PD patients in active and inactive treatment arms of clinical trials, to quantify and discern symptomatic and disease‐modifying treatment effects, and to demonstrate how model‐based methods may be used to design clinical trials. The historical lack of efficiency of PD clinical trials begs for model‐based simulations in planning for studies that result in more informative conclusions, particularly around disease modification. © 2016 International Parkinson and Movement Disorder Society